An Overview of Prospective Brides’ Preconceptional Health Using “Elsimil Application” - Tazkiyah, Nadya Dina; Suprapti; Wulandari, Lisa Purbawaning; Mansur, Herawati; Sunaeni (Futurity Medicine, 2024)
Preconceptional health has significant effect on pregnancy outcomes. Preconceptional health should be identified during premarital screening to allow brides sufficient time to enhance their health status. Aims: The objective of this study was to assess the preconceptional health characteristics of potential brides in Malang Regency using "Elsimil application". Study design: A quantitative descriptive research methodology was employed in the study, utilising a secondary data analysis approach. Place and Duration of Study: The data for the study was obtained from potential brides who completed the premarital screening questionnaire on the Elsimil Application between January and May 2022 in Malang, Indonesia. Methodology: The used sampling technique was the total sampling technique. The variables studied were prospective bride's preconceptional health with sub-variables: age, BMI, Hb levels, upper arm circumference, and smoking behaviour which were collected using an instrument in the form of a checklist table. Results: The findings of the descriptive statistical analysis, which included the investigation of the frequency and percentage, revealed that a significant proportion of potential brides in Malang Regency over the period of January to May 2022, who participated in the "Elsimil" premarital screening questionnaire, exhibited a preconception health state that was deemed to be at risk (61.1%). Scientific Novelty: This research introduces the use of the Elsimil Application to improve the preconception health of prospective brides and grooms. Its novelty lies in the integration of digital technology to monitor health, provide health education, analyse risk data, and evaluate the effectiveness of applications in real practice, which has a positive impact on maternal and child health. Conclusion: Premarital screening providers need to monitor prospective brides until their preconception health status is ideal.